Critical Studies of Multimodal and Multimedia Discourse (ECDMM): a route of analysis in a contemporary perspective. - Rodríguez Flechas, Camilo Alejandro (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2024)
In this text, from the perspective of Critical Studies of Multimodal and Multimedia Discourse (ECDMM), some of the theoretical principles that guide their reflections, some epistemological principles of the methodology and a type of method previously adopted that can serve as input for future research, taking as a reference the local and global challenges that arise in contemporary times.